The significance of the isolation of Corynebacterium species from urine of patients at Baragwanath Hospital. - Walkden, Deborah Dianne (My University, 1993)
The purpose of this study was firstly to determine whether corynebacteria, when isolated from urine specimens, represent significant pathogens and secondly to atternpt to increase the isolation rate of Corynebacterium urealyticum, a known urinary pathogen by culturing urine specimens on a selective medium. An attempt was made to identify all isolates of corynebacteria to the species level and antimicrobial susceptibility testing was performed on all organisms. (Abbreviation abstract)
A Dissertation Submitted to the University of the Witwatersrand, Jobannesburg. for the degree of Master of Medicine in Microbiology.
Keywords: Corynebacterium.